Inbreeding removes sex differences in lifespan in a population of Drosophila melanogaster - Carazo, P; Green, J; Sepil, I; Pizzari, T; Wigby, S (Royal Society, 2016)
Sex differences in ageing rates and lifespan are common in nature, and an enduring puzzle for evolutionary biology. One possibility is that sex-specific mortality rates may result from recessive deleterious alleles in “unguarded” heterogametic X or Z sex chromosomes (the unguarded X hypothesis). Empirical evidence for this is, however, limited. Here, we test a fundamental prediction of the unguarded X hypothesis in Drosophila melanogaster, namely that inbreeding shortens lifespan more in females (the homogametic sex in Drosophila) than in males. To test for additional sex-specific social effects, we studied the lifespan of males and females kept in isolation, in related same-sex groups, and in unrelated same-sex groups. As expected, outbred females outlived outbred males and inbreeding shortened lifespan. However, inbreeding-mediated reductions in lifespan were stronger for females, such that lifespan was similar in inbred females and males. We also show that the social environment, independent of inbreeding, affected male but not female lifespan. In conjunction with recent studies, the present results suggest that asymmetric inheritance mechanisms may play an important role in the evolution of sex-specific lifespan and that social effects must be considered explicitly when studying these fundamental patterns.